EMPOWERING PANDAN ARUM BATIK: THE ROLE OF COLOR GUIDEBOOKS IN DESIGN AND SUSTAINBILITY - Kusumawati, Yudhistya Ayu; Lasmy, Lasmy; Widita, Anindya; Qurma, Alya Al (Bina Nusantara University, 2025)
Pandan Arum Batik is one of the batik industries located in Pandanmulyo Village, Malang Regency. This home-based batik industry produces various kinds of batik with various techniques, namely written batik, stamped batik, and now expanding to ecotik (eco-print batik). Based on the situation analysis, several problems were found, including those related to production aspects. Community service with the Appropriate Technology scheme aims to increase human resource capacity in developing color guidebooks to elevate batik products. In this community service activity, the service team provides intensive counseling and assistance to partners regarding the use of natural dyes in batik production and the using of color combination through color theory. This community service is very important to help batik industry increase their productivity. It is hoped that this community service activity can help the batik industry become more productive. The output of this community service activity is implementing color guidebooks that partners can use to elevate their batik through color science.